Vapor‐Phase Linker Exchange of the Metal–Organic Framework ZIF‐8: A Solvent‐Free Approach to Post‐synthetic Modification. (4th November 2019) - Marreiros, João; Van Dommelen, Lenz; Fleury, Guillaume; de Oliveira‐Silva, Rodrigo; Stassin, Timothée; Iacomi, Paul; Furukawa, Shuhei; Sakellariou, Dimitrios; Llewellyn, Philip L.; Roeffaers, Maarten; Ameloot, Rob
Abstract: Zeolitic imidazolate frameworks (ZIFs) are a sub‐class of metal–organic frameworks (MOFs). Although generally stable, ZIFs can undergo post‐synthetic linker exchange (PSLE) in solution under mild conditions. Herein, we present a novel, solvent‐free approach to post‐synthetic linker exchange through exposure to linker vapor. Abstract : Mach Dampf ! Obwohl allgemein stabil, können zeolithische Imidazolatgerüste (ZIFs) unter milden Bedingungen in Lösung einem post‐synthetischen Linkeraustausch (PSLE) unterzogen werden. Hier wird ein neuartiger, lösungsmittelfreier Ansatz zum PSLE durch Einwirkung von Dämpfen der Linker vorgestellt.